Factors Leading to Cesarean Section Delivery at Tarakan Hospital, North Kalimantan - Padlilah, Rahmi; Yulianti, Ika; Ariyanti, Ririn (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2021)
Background: